2020
DOI: 10.1111/epi.16690
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Fenfluramine hydrochloride for the treatment of seizures in Dravet syndrome: A real‐world study

Abstract: Objective: Dravet syndrome (DS) is a drug-resistant, infantile onset epilepsy syndrome with multiple seizure types and developmental delay. In recently published randomized controlled trials, fenfluramine (FFA) proved to be safe and effective in DS. Methods: DS patients were treated with FFA in the Zogenix Early Access Program at four Italian pediatric epilepsy centers. FFA was administered as add-on, twice daily at an initial dose of 0.2 mg/kg/d up to 0.7 mg/kg/d. Seizures were recorded in a diary. Adverse ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 32 publications
8
37
2
Order By: Relevance
“…25 It was also a commonly observed AE in our study and the Italian study, but in only 22% and 13% of patients, respectively; only one patient discontinued due to this AE in our study and none in the Italian study. In addition, in agreement with other studies, 16,25 we also commonly observed somnolence, although it only resulted in one patient discontinuing FFA. There were no cases of sudden unexpected death in epilepsy (SUDEP) and no deaths during the FFA treatment period, although evaluating the effects of FFA on SUDEP and mortality requires a study with a larger population and a longer surveillance period.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…25 It was also a commonly observed AE in our study and the Italian study, but in only 22% and 13% of patients, respectively; only one patient discontinued due to this AE in our study and none in the Italian study. In addition, in agreement with other studies, 16,25 we also commonly observed somnolence, although it only resulted in one patient discontinuing FFA. There were no cases of sudden unexpected death in epilepsy (SUDEP) and no deaths during the FFA treatment period, although evaluating the effects of FFA on SUDEP and mortality requires a study with a larger population and a longer surveillance period.…”
Section: Discussionsupporting
confidence: 93%
“…It is also notable that during treatment with FFA in our study, 45% of patients were able to discontinue concomitant ASMs, and the dose was tapered in a further 23% of patients. Specchio et al 16 also reported reductions in the medication burden (discontinuations or dose reductions of concomitant ASMs) with FFA in 46% of patients, although the proportion of patients who discontinued an ASM was lower than in our study (14% vs. 45%). This may be due to the longer follow‐up in our study, allowing more time to assess whether the patient had achieved a sustained period of seizure control before discontinuing concomitant ASMs.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Other fenfluramine trials also observed a significant reduction in MCSF in children and young adults. These studies showed a higher dose of fenfluramine extended the amount of days without a seizure, relative to a smaller dose [47][48][49][50]. Fenfluramine has just been approved by FDA for use in patients with DS.…”
Section: Treatmentmentioning
confidence: 99%